2015
DOI: 10.1016/j.bjorl.2015.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Oral cavity squamous cell carcinoma: factors related to occult lymph node metastasis

Abstract: Metastatic disease rate was similar to that found in the literature. Perineural and angiolymphatic invasion and tumor thickness were associated with occult metastasis, but only angiolymphatic invasion showed to be an independent risk factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
17
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 31 publications
(46 reference statements)
6
17
0
7
Order By: Relevance
“…However, to our knowledge, this is the first study to evaluate tumor thickness and its influence on the overall survival rates of patients with recurrent oral cavity cancers. Other publications from our group showed that a tumor thickness >7 mm in the oral cavity was associated with a higher incidence of lymph node metastasis, and that lesions >10 mm were associated with shorter disease‐free survival . The cutoff value of 10 mm for tumor thickness as a risk factor for shorter survival rates also reflects the results from our previously reported series .…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…However, to our knowledge, this is the first study to evaluate tumor thickness and its influence on the overall survival rates of patients with recurrent oral cavity cancers. Other publications from our group showed that a tumor thickness >7 mm in the oral cavity was associated with a higher incidence of lymph node metastasis, and that lesions >10 mm were associated with shorter disease‐free survival . The cutoff value of 10 mm for tumor thickness as a risk factor for shorter survival rates also reflects the results from our previously reported series .…”
Section: Discussionsupporting
confidence: 84%
“…However, some authors have demonstrated that the recurrences usually occur before 18 months. In a previous study from our institution, d'Alessandro et al found that 92.8% of locoregional recurrences occurred within the first 12 months of follow‐up in patients with tumors of the oral cavity and oropharynx after primary treatment. In the present study, 33.3% of these patients also had a new recurrence in the first 12 months.…”
Section: Discussionmentioning
confidence: 93%
“…This reflects the challenge of obtaining free margins when operating on high‐volume tumors that are not confined by cartilaginous or osseous boundaries . However, margin positivity was not a predictor of recurrence or death, even on univariate analysis, as well as other features usually associated with poor prognosis, such as angiolymphatic invasion and lymph node extracapsular spread, were also not relevant prognostic factors in the present study, as demonstrated in other studies by our group …”
Section: Discussionsupporting
confidence: 66%
“…Interestingly, this trend occurred along all N classifications, but N0 tumors presented with larger volumes. The common belief that lymph node metastasis occurs more frequently in larger tumors does not seem to apply in already advanced tumors, as shown in our series . We found no report of such a paradoxical association in the literature.…”
Section: Discussionsupporting
confidence: 49%
“…However, analysis of recent articles, especially those reporting large case series or meta‐analyses, seems to support elective/stadiative neck dissection as the recommended treatment given the remarkable rate of occult neck metastasis observed . The reported rate is variable, ranging from 7% to 42%, although most authors have reported that neck dissection also improves locoregional control in patients with N0 cancer …”
Section: Discussionmentioning
confidence: 99%